2018
DOI: 10.1080/17461391.2018.1472811
|View full text |Cite
|
Sign up to set email alerts
|

Interval running with self‐selected recovery: Physiology, performance, and perception

Abstract: This study (1) compared the physiological responses and performance during a high-intensity interval training (HIIT) session incorporating externally regulated (ER) and self-selected (SS) recovery periods and (2) examined the psychophysiological cues underpinning SS recovery durations. Following an incremental maximal exercise test to determine maximal aerobic speed (MAS), 14 recreationally active males completed 2 HIIT sessions on a non-motorised treadmill. Participants performed 12 × 30 s running intervals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Researchers have attempted to use self-selected recovery durations as a method of individualisation demonstrating the method to be effective when participants are well familiarized with the procedures and physical demands of the HIIT protocol 4,5,[8][9][10] . While selfselected recovery durations take into consideration the day-to-day variation in the individuals environmental and/or psychological state 8,10,11 , it does not take into account the individuals' recovery status in order to recommence exercise. If the individual's physiological status during recovery is not considered it could lead to inadequate or excessive recovery between work intervals, potentially compromising the training session.…”
mentioning
confidence: 99%
“…Researchers have attempted to use self-selected recovery durations as a method of individualisation demonstrating the method to be effective when participants are well familiarized with the procedures and physical demands of the HIIT protocol 4,5,[8][9][10] . While selfselected recovery durations take into consideration the day-to-day variation in the individuals environmental and/or psychological state 8,10,11 , it does not take into account the individuals' recovery status in order to recommence exercise. If the individual's physiological status during recovery is not considered it could lead to inadequate or excessive recovery between work intervals, potentially compromising the training session.…”
mentioning
confidence: 99%
“…Session characteristics varied substantially between participants, suggesting varying 'ideals' in terms of work and recovery characteristics. McEwan et al (2018) reported large inter-individual variability in recovery duration during self-regulated interval running, attributing this in part to individual differences in afferent cues used to regulate recovery durations. Use of varied afferent cues alongside variability in recovery durations between work bouts supports the contention that externally prescribing a standard recovery duration is inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Health improvements are optimised when exercise intensity is tailored to individual capacity (McPhee, Williams, Degens, & Jones, 2010), which has stimulated work into self-regulation of recovery duration during HIIT (McEwan, Arthur, Phillips, Gibson, & Easton, 2018;Phillips, Thompson, & Oliver, 2014). The concept of self-regulating recovery is important considering the large individual variability in required recovery time between high-intensity exercise bouts (McEwan et al, 2018), which indicates that externally imposed recovery periods may be inappropriate for optimising physical and, perhaps, perceptual responses to HIIT (Ekkekakis et al, 2011). The available evidence suggests that individuals are able to self-regulate recovery in a reliable fashion in order to meet the goals of a HIIT session (Phillips et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a number of studies have used self-selected (SS) recovery durations in HIIT protocols, in which athletes started subsequent work intervals when they felt 'adequately recovered to exercise at the required intensity'. [5][6][7][8][9][10] While a considerable amount of variation was evident in SS recovery durations across different HIIT protocols, and SS recovery time is potentially dependent on maturation status 7,10 (see figure 1), the current understanding is that athletes can adequately select recovery durations to achieve the required exercise intensities in subsequent work intervals in both RST and SIT (see figure 1) and AIT (see figure 2).…”
Section: Characteristics Of All Reviewed Studies Are Summarized In Sumentioning
confidence: 99%
“…20 In SIT protocols similar beneficial performance outcomes were reported across a multitude of exercise modalities when recovery duration was increased between work intervals. 8,[21][22][23] McEwan et al, 8 compared the acute physiological responses and running performance in 12 × 30 sec sprints, wherein the recovery duration was either fixed (30 sec) or self-selected (SS). SS recovery time increased over the protocol (see figure 1) and averaged 51±15 sec.…”
Section: The Recovery Duration During Rst and Sitmentioning
confidence: 99%